2009
DOI: 10.1063/1.3274137
|View full text |Cite
|
Sign up to set email alerts
|

InGaN multiquantum well structure with a reduced internal electric field and carrier decay process by tunneling

Abstract: An InGaN/InGaN multiquantum well (MQW) structure with a reduced internal electric field is grown, and compared with a conventional InGaN/GaN MQW structure. Time-integrated and time-resolved photoluminescence (PL) are measured as a function of an external bias voltage. The flatband condition, in which the external bias voltage completely compensates the internal electric field, is found by a measurement of PL peak energy as a function of bias voltage. From the measurement of the integrated PL intensity and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…This indicates that band-bending across M11 is less than that of R01, and polarization field of M11 is reduced. Thorough TRPL analysis showed that polarization field of an LED with MLBs was actually reduced compared to the reference LED by around 19%, 9 It is confirmed that the MLB structure actually reduces polarization field across wells.…”
mentioning
confidence: 82%
“…This indicates that band-bending across M11 is less than that of R01, and polarization field of M11 is reduced. Thorough TRPL analysis showed that polarization field of an LED with MLBs was actually reduced compared to the reference LED by around 19%, 9 It is confirmed that the MLB structure actually reduces polarization field across wells.…”
mentioning
confidence: 82%
“…The tunneling time is determined by the effective barrier width and potential barrier height of the triangular-shaped energy band subject to an external bias voltage. 11,12 The tunneling time of sample B was longer by almost an order of magnitude than that of sample A, which was attributed to the higher potential barrier due to higher indium composition in the MQW. In addition, the piezoelectric field is known to have an adverse effect on the tunneling rate since it makes electrons and holes travel in opposite directions to which they contribute to the photocurrent.…”
mentioning
confidence: 95%
“…12,15 In addition, the tunneling time can be shorter than the recombination time at a certain voltage because of a sharper triangular barrier having a reduced barrier thickness. 11 The carrier lifetime of the two samples became shorter as the reverse bias increased after a certain voltage. For sample A, the carrier lifetime decreased rapidly from 3.4 ns to 0.29 ns when we change the bias from 1 V to À5 V. Decay time looked constant at below $À3 V due to the equipment resolution limit (39 ps) but it is expected to be shorter than the measured value.…”
mentioning
confidence: 99%
“…The large strain within the active region will result in the energy band of QWs being severely bended and the reduction in the electron-hole wave-function overlap, leading to a strong quantum-confined Stark effect (QCSE) and poor internal quantum efficiency (IQE). Therefore, several specific structural designs, such as InGaN interlayer [5], graded MQWs [6], chirped MQWs [7], staggered InGaN QWs [8,9], AlGaInN barrier [10,11], InGaN barrier [12], indium pre-deposition [13], and Si-doped barriers [14], have been performed to alleviate piezoelectric polarization field in the MQWs and increase the radiative recombination rate, resulting in the enhancement of IQE.…”
Section: Introductionmentioning
confidence: 99%